Effects of irrigation and nitrogen fertilizer on yield, carbon inputs from above ground harvest residues and soil organic carbon contents of a sandy soil in Germany. (9th May 2014) - Trost, B.; Ellmer, F.; Baumecker, M.; Meyer‐Aurich, A.; Prochnow, A.; Drastig, K.; Goss, Michael
Abstract To better understand the complex interactions between irrigation and nitrogen fertilizer application on soil organic carbon content, the results from long‐term field experiments over a period of 40 years were analysed. The combined effect of irrigation and nitrogen fertilizer rates on crop yields, carbon input by above ground harvest residues and soil organic carbon content has been investigated at a site on a sandy soil in northeast Germany. Combined with nitrogen fertilizer application, irrigation has frequently had a significantly positive effect on crop yield and carbon inputs from above ground harvest residues. However, enhanced carbon inputs to the soil under irrigation did not lead to significantly greater soil organic carbon contents. As the combination of irrigation and nitrogen also improved microbial decomposition by changing of above ground harvest residues C/N ratio and soil moisture, the effect of an additional input of carbon from above ground harvest residues was nullified.